A CASE OF 13-YEAR-OLD GIRL WITH PROLIDASE DEFICIENCY - Khushdil, Arshad; Murtaza, Fatima (Journal of Ayub Medical College Abbottabad, 2017)
Prolidase deficiency is a rare autosomal recessive disorder characterized by recurrent and non-healing skin ulcers along with facial dysmorphism and mental retardation. We report a 13-year-old girl who has clinical manifestation of Proliodase deficiency. It is a very rare disorder and no such case has been reported so far fromPakistan. Keywords: Autosomal recessive disorder; Prolidase deficiency; Facial dysmorphism